Pengaruh Customer Experience dan Persepsi Kegunaan Terhadap Minat Penggunaan Ulang Aplikasi E-Commerce Minimarket Alfagift: Studi Kasus Pengguna Aplikasi Alfagift Pada Followers Instagram @alfagift_idn - Putri, Eka Yulia; Kadunci; Rosalina, Erlyn (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2024)
This study aims to examine, determine, and analyze the influence of customer experience and perceived usefulness on the intention to reuse the Alfagift minimarket e-commerce application on Alfagift application users, especially Instagram followers @alfagift_idn. This study uses a quantitative approach involving one hundred respondents as samples and processed using SPSS 26. This research implies that the data fullfill the requirements of a normal distribution, which is 0.200> 0.05. The regression equation model in this study is Y = 18.986 + 0.404 X1 + 0.388 X2 + e, so the research stated that the data in this study is viable to use. According to the data results of the partial correlation, the customer experience variable has an impact on the intention to reuse by 61.31% and the perception of usefulness has an impact on the intention to reuse by 62.09%. According to the results of the determination coefficient analysis (), 66.1% of the intention to reuse the Alfagift application is influenced by the independent variables, namely customer experience and perception of usefulness. Hypothesis testing in this study shows a positive and significant influence both partially and simultaneously.